The quality of sport- recreation services with regard of fitness club for women - Agnieszka Widawska-Stanisz (Nicolaus Copernicus University in Toruń, 2016)
The aim of this article was showing the meaning of quality in the service activity of sport- recreation companies. Taking under consideration current research concerning the forms of spending free time, health-promoting lifestyle, trends of physical activity, searching of new ways of fulfilling these needs, it is worth noticing the potential of sport-recreation branch. Additionally, it is worth mentioning that the market of sport- recreation services in Poland is flaked and Polish receivers more often look for services totally fulfilling their needs and high quality services. There is an example of function the chain of fitness clubs for women in this article, and the trial of attempt of diagnosing the determiners influencing the level of quality sport-recreation services.